EVALUATING ASSESSMENT POLICIES AND PRACTICES OF INTERNATIONAL SCHOOL OF PARIS (ISP) - Marina Marina; Kurniawati Kurniawati; Dini Rizki (Jurnal Dedikasi Pendidikan, 2021)
International Baccalaureate (IB) is a foundation that is headquartered in Geneva whose focus is to foster critical thinking and building problem-solving skills. Its programmes encourages diversity, international mindedness, curiosity and a healthy appetite for learning and excellence. This foundation develops the assessment policies and practices in International School of Paris (ISP). This paper attempts to evaluate the assessment policies implemented in the school. There are four sections mentioned in the ISP assessment policy i.e. assessment principles, assessment purpose, assessment practices and grading practices. The primary focus of this paper is the practice of three ISP assessment sources: ongoing formative teacher assessments, summative assessment tasks and the student as learner. The evaluation of each sources is reviewed and discussed.